Use of supplements by Japanese elite athletes for the 2012 Olympic Games in London - Sato, A.; Kamei, A.; Kamihigashi, E.; Dohi, M.; Akama, T.; Kawahara, T. (Clinical Journal of Sport Medicine, 2015)
Objective: To investigate supplement use among Japanese elite athletes. Design: We conducted a cross-sectional survey study using individual interviews during athletes' medical evaluations. Setting: One to 5 months before the Olympic Games in 2012, London, United Kingdom. Participants: Five hundred fifty-two Japanese athletes for the London Games, including candidates. Independent Variables: Sex, sports, supplement category, and participation. Main Outcome Measures: Whether athletes used supplements, what products were used, the frequency and purposes of use, and from what sources athletes received information on supplements. Results: All 552 athletes were interviewed by pharmacists regarding supplement use and agreed to the survey. Of them, 452 (81.9%) used 1 or more supplement products in the year before the study; a total of 952 different products (mean = 1.7, SD = 1.4) were used. The most commonly used supplement was amino acids (310 athletes; 56.2%), and 358 (38.7%) of the total products were amino acids. Of the athletes, 241 (43.7%) took at least 1 supplement daily, and of the supplements, 457 (49.4%) were taken daily. The most common purpose for supplement use was recovery from fatigue—327 (59.2%) athletes chose this answer, and 486 (52.5%) products were used for this purpose. Finally, regarding athletes' information sources on supplements, coaches, managers, and trainers were the most frequent advisors (275 athletes, 49.8%; 466 products, 50.4%). Conclusions: The results revealed widespread supplement use among Japanese elite athletes for the London Olympic Games. Education system was required not only for athletes but also for athletes' entourage, such as coaches, managers, trainers, and supplement companies. Clinical Relevance: This study will provide basic data for establishing an education system that would better guide athletes' use of supplements.